Effect of Therapeutic Hypothermia Initiated After 6 Hours of Age on Death or Disability Among Newborns With Hypoxic-Ischemic Encephalopathy: A Randomized Clinical Trial. Issue 3 (March 2018) - Laptook, Abbot R.; Shankaran, Seetha; Tyson, Jon E.; Munoz, Breda; Bell, Edward F.; Goldberg, Ronald N.; Parikh, Nehal A.; Ambalavanan, Namasivayam; Pedroza, Claudia; Pappas, Athina; Das, Abhik; Chaudhary, Aasma S.; et al.
Abstract : (Abstracted from JAMA 2017;318(16):1550–1560) Hypoxic-ischemic neonatal encephalopathy can cause mortality and devastating lifelong cerebral palsy, neurosensory deficits, and cognitive impairments in neonates. Therapeutic hypothermia initiated within 6 hours after birth has been found to reduce the risk of death or disability at 18 months for hypoxic-ischemic encephalopathy.